Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ijc.24800
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein‐1 (MCP‐1)/CCL2 secreted by hepatic myofibroblasts promotes migration and invasion of human hepatoma cells

Abstract: The aim of our study was to investigate whether myofibroblasts and the chemokine monocyte chemoattractant protein-1 (MCP-1)/CCL2 may play a role in hepatocellular carcinoma progression. We observed that hepatic myofibroblast LI90 cells express MCP-1/CCL2 mRNA and secrete this chemokine. Moreover, myofibroblast LI90 cell-conditioned medium (LI90-CM) induces human hepatoma Huh7 cell migration and invasion. These effects are strongly reduced when a MCP-1/CCL2-depleted LI90-CM was used. We showed that MCP-1/CCL2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 62 publications
(79 reference statements)
6
47
0
1
Order By: Relevance
“…We found that MCP-1 secreted by CAFs promoted OSCC cell invasion and migration by binding to its receptor, CCR2, indicating a direct effect of MCP-1 on tumor malignancy. Recent studies (38,39) showing that MCP-1 directly induces prostate and hepatic tumor cell invasion and migration support our findings. Our results imply a critical role for MCP-1/CCR2 signaling in cell invasion and migration; therefore, blocking MCP-1/ CCR2 signals may attenuate OSCC metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…We found that MCP-1 secreted by CAFs promoted OSCC cell invasion and migration by binding to its receptor, CCR2, indicating a direct effect of MCP-1 on tumor malignancy. Recent studies (38,39) showing that MCP-1 directly induces prostate and hepatic tumor cell invasion and migration support our findings. Our results imply a critical role for MCP-1/CCR2 signaling in cell invasion and migration; therefore, blocking MCP-1/ CCR2 signals may attenuate OSCC metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…MCP-1 is a member of the small inducible gene family, and plays a role in the recruitment of monocytes to sites of injury and infection, its expression may plausibly be associated with HCC development (18).The current study showed a highly significant increase in the serum level of MCP-1 in HCC patients in comparison with other groups. The results are similar to that of Wang et al, (19) who found that serum MCP-1 levels were significantly higher in the HCC group than in the cirrhotic group or the controls.…”
Section: Discussionsupporting
confidence: 49%
“…152 Moreover, CCL2 treatment enhances the migration and invasion of Huh7 hepatoma cells in vitro. 153 Macrophageand biliary epithelial cell-produced CCL3 is also upregulated in the fibrotic liver and expression of CCR1 and CCR5 has been detected on effector T cells within lymphoid-like follicles. 53 CCL3 appears to be an important mediator of injuryinduced liver fibrosis as demonstrated by the reduction in immune cell infiltration and attenuation of fibrosis in CCL3-deficient mice.…”
Section: Activatedmentioning
confidence: 99%